The Role of Endoscopic Ultrasound in the Diagnosis and Management of Primary Gastric Lymphoma. (16th March 2017) - Schizas, Dimitrios; Ntanasis-Stathopoulos, Ioannis; Tsilimigras, Diamantis I.; Sioulas, Athanasios D.; Moris, Demetrios; Spartalis, Eleftherios; Scotiniotis, Ilias; Papanikolaou, Ioannis S.
Abstract : Endoscopic ultrasound (EUS) is considered a valuable diagnostic tool during the workup of malignant gastric lesions, including primary gastric lymphomas (PGL). Although endoscopy combined with multiple biopsies remains essential in the establishment of PGL diagnosis, EUS utilization in locoregional disease staging has been well documented in the literature. Data also support the possible role of EUS in prediction of response to first-line treatment, that is, Helicobacter pylori eradication. However, its application in the posttreatment setting remains problematic, since concordance rates between endosonography and histology findings during follow-up seem to vary substantially. The aim of the present review is to summarize all available data regarding the role of EUS in the management of PGL.